Balibe Mountain Stone Worker Women: Innovation in Science and Technology of Mining Waste Crafts to Improve the Welfare of Bonder Village, West Praya District - Andiana, Baiq Dewi Lita; Herdiana, Herdiana; Meidatuzzahra, Diah (Pascasarjana Universitas Mataram, 2024)
The development and progress of the world towards the end of the 21st century has raised the issue of gender. This issue of gender has become a debate among many circles. Gender is a term used to describe the distinction between men and women. In a society that adheres to a patriarchal system, the economic function of the family is played by the husband as the head of the household, while the existence of a woman is identical to domestic work in the household. The pressure of economic needs is a real challenge that must be addressed by the family, including encouraging the role of women to help with the economic function of the household. When women work outside the home, especially as stone breakers, there is a shift in roles and functions that are certainly inherent in the understanding of women as part of their self-existence. Women stone breakers who work around the Balibe rock mountain are a group of women housewives who are poorly educated and have no skills. Economic pressure is the main reason they become stone breakers. This community service activity aims to provide innovation and education to groups of women farm workers in improving soft skills to improve quality, through counseling and training. The location of the community service activity is in Bonder Village, Praya Barat District, Central Lombok Regency-NTB. With partners of the Balibe stone labor group totaling 15 people. This activity is strongly supported by partners and all communities at the research location. The involvement of partners in this activity is in the training activities for making handicrafts from mining waste, partners collect stones that are unique in shape and can be formed as basic materials for making crafts. There are several crafts made, namely frames, flower vases, bamboo gazebos. In this activity, the equipment provided is in the form of stone-breaking business equipment including hammers, protective glasses, gloves, hammers and Japanese hats